LITERASI DIGITAL SERTA PERANANNYA DALAM MENINGKATKAN PEREKONOMIAN RAKYAT DI SITUBONDO - Ediyanto Ediyanto; Alfisatun Nadira; Siti Nurholifah; Musleh Musleh; Nur Laila Septiana (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study investigates how digital literacy contributes to strengthening community economic development in Situbondo. The rapid advancement of information and communication technology has reshaped how people access information, perform transactions, manage businesses, and utilize public services. Despite the widespread availability of smartphones, digital literacy levels in Situbondo remain uneven and largely basic. Limited understanding of digital security, online transactions, and the economic use of digital tools prevents the community from fully benefiting from digital transformation. Using a qualitative descriptive method, data were gathered from observations, reports, and relevant literature to examine digital literacy levels, economic conditions, barriers to digital transactions, and their relationship with community economic activities. The findings reveal that digitalization has begun to support local economic growth, particularly among MSMEs that employ digital platforms for marketing and business operations. However, challenges persist, including unstable internet access, low digital skills, concerns over privacy and fraud, and insufficient knowledge of digital financial services. These issues reduce public trust in adopting digital transactions. The study also demonstrates a positive relationship between higher levels of digital literacy and increased participation in digital economic activities. Individuals with stronger digital competencies tend to expand their market reach, improve operational efficiency, and unlock greater income opportunities. Overall, enhancing digital literacy is crucial for advancing economic empowerment in Situbondo. Continuous training, improved infrastructure, and targeted support for MSMEs are necessary to maximize the benefits of digital transformation and strengthen the region’s economic resilience.